De la imposibilidad del laicismo - Castellanos Rodríguez, Belén (Nómadas. Critical Journal of Social and Juridical Science, 2010)
This article tries to show the religious burden of the secular policies similar to those of the French model. We would like to note that, on behalf of secularity, ethnocentrism is being promoted and the xenophobic policies targetting to difficult the life of a big number of immigrants are covered. We wish to point the fact that, lately, the secular policies really hide anti-Islam policies. We finally propose the philosophical spirit as opposed to the ideology of secularity.